Preparation method and application of PbTe-based thermoelectric material

CN122979684APending Publication Date: 2026-10-27UNIV OF ELECTRONICS SCI & TECH OF CHINA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611156929.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-31
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

然而,采用过量Pb掺杂难以有效降低热导率,而仅依靠Zn掺杂又会导致载流子迁移率下降

Benefits of technology

[0027]本发明至少包括以下有益效果:本发明通过在n型PbTe中引入过量Pb,并协同掺杂Zn元素,制备得到Pb1+x-yTe0.996I0.004-yZn,通过精确调控Pb过量浓度(x= 0.002~0.012)和Zn掺杂量(y=0.01~0.04),结合真空封管工艺和多阶段烧结技术,实现了“缺陷修复-载流子输运-声子散射”的协同优化,解决了传统PbTe热电材料迁移率低、热导率高的问题,显著提升了n型PbTe的热电性能,同时工艺简单可控,适用于规模化生产,在中高温热电转换领域具有重要应用前景,为开发高性能热电材料提供了创新解决方案。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122979684A_ABST
    Figure CN122979684A_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of PbTe-based thermoelectric material, comprising the following steps: mixing and grinding Pb powder, Te powder, PbI2 powder and Zn powder to obtain mixed powder; loading the mixed powder into a quartz tube and vacuum sealing the tube; high-temperature melting and water quenching the sealed quartz tube to obtain an ingot; crushing and grinding the ingot; and discharging plasma sintering the powder to obtain the PbTe-based thermoelectric material. 1+x‑y Te 0.996 I 0.004 - y Zn. The introduction of excess Pb into the n-type PbTe effectively reduces the scattering of carriers by Pb vacancies, significantly improving the mobility; Zn doping forms a nanoscale ZnTe heterophase in the matrix, enhancing phonon scattering and reducing lattice thermal conductivity. The bulk material prepared by the solid phase reaction method and the discharge plasma sintering has a density higher than 97%, and the thermoelectric figure of merit ZT can reach more than 1.08 at 823K, solving the problems of low mobility and high thermal conductivity of traditional PbTe thermoelectric materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of thermoelectric materials technology, and more specifically, this invention relates to a method for preparing and applying a PbTe-based thermoelectric material. Background Technology

[0002] Thermoelectric materials enable the direct conversion between thermal and electrical energy, showing significant application potential in fields such as industrial waste heat recovery and automotive exhaust power generation. Among them, n-type PbTe (lead telluride) exhibits superior thermoelectric performance in the mid-to-high temperature range (500-900K) due to its unique band structure and excellent electrical transport properties. However, traditional n-type PbTe materials suffer from intrinsic Pb vacancy defects, which severely limit carrier mobility and electrical conductivity. Furthermore, the material's inherently high thermal conductivity is also a crucial factor restricting further improvements in its thermoelectric performance.

[0003] Excess Pb can fill intrinsic vacancy defects, effectively reducing carrier scattering and improving mobility. Zn doping, on the other hand, enhances phonon scattering and reduces thermal conductivity by forming a nanoscale ZnTe precipitate. However, excessive Pb doping is insufficient to effectively reduce thermal conductivity, while relying solely on Zn doping leads to a decrease in carrier mobility. Furthermore, traditional fabrication processes suffer from issues such as inappropriate sintering regimes, which limit the stability and repeatability of material properties.

[0004] Therefore, how to effectively reduce thermal conductivity while maintaining high carrier mobility by synergistically optimizing the ratio of excessive Pb doping to Zn doping has become a key challenge in the current research of PbTe thermoelectric materials. Summary of the Invention

[0005] One object of the present invention is to solve at least the above-mentioned problems and / or defects, and to provide at least the advantages described below.

[0006] To achieve these objectives and other advantages of the present invention, a PbTe-based thermoelectric material is provided, the chemical composition of which is PbTe. 1+x-y Te 0.996 I 0.004 - y Zn; where, x The value is between 0.002 and 0.012. y The value is between 0.01 and 0.04.

[0007] Preferably, the Pb 1+x-y Te 0.996 I 0.004 - y In Zn, x It is 0.010. y It is 0.02.

[0008] Preferably, the PbTe-based thermoelectric material has a thermoelectric figure of merit ZT ≥ 1.08 at 823 K.

[0009] Preferably, the PbTe-based thermoelectric material has a density ≥97% and a grain size of 20~50μm.

[0010] A method for preparing a PbTe-based thermoelectric material as described above includes the following steps: Step 1: Mix and grind Pb powder, Te powder, PbI2 powder and Zn powder to obtain a mixed powder; Step 2: Load the mixed powder into a quartz tube and seal it under vacuum; Step 3: The sealed quartz tube from Step 2 is subjected to high-temperature melting, water quenching and cooling, and annealing to obtain an ingot; Step 4: Crush and grind the ingot prepared in Step 3 into powder; Step 5: Perform spark plasma sintering on the powder from Step 4 to obtain PbTe-based thermoelectric material PbTe. 1+x- y Te 0.996 I 0.004 - y Zn.

[0011] Preferably, in step one, the grinding is carried out under argon protection for 20 to 60 minutes, with a 2-minute pause every 5 minutes of grinding.

[0012] Preferably, in step two, the specific steps of vacuum sealing include: loading the mixed powder into the quartz tube, connecting it to the vacuum system, and evacuating it to a vacuum level of 1×10⁻⁶. -4 ~1×10 -3 Pa, is sealed using an oxyhydrogen flame.

[0013] Preferably, in step three, the specific steps of high-temperature melting include: heating to 573-773K at a heating rate of 3-10K / min, holding at that temperature for 0.5-2 hours, then heating to 1173-1373K and holding at that temperature for 4-8 hours.

[0014] Preferably, in step three, the specific steps of water quenching include: taking out the quartz tube, immersing it in ice-salt water for quenching, and the cooling rate is 100~300K / s.

[0015] Preferably, in step three, the annealing process includes: heating the water-quenched quartz tube to 773-973K at a rate of 1-10K / min and holding it at that temperature for 36-60 hours.

[0016] Preferably, in step four, the material is crushed and ground until it passes through a 200-400 mesh sieve.

[0017] Preferably, step four further includes: doping modified carbon nanotubes into the powder and ball milling to obtain a doped mixed powder.

[0018] Preferably, the mass ratio of the powder to the modified carbon nanotubes is 99.7~99.9:0.1~0.3.

[0019] Preferably, the specific method of ball milling is as follows: bidirectional ball milling for 180-300 minutes under argon protection, ball-to-material ratio of 15-25:1, forward and reverse rotation at 200-400 r / min, with a 5-minute pause every 15 minutes.

[0020] Preferably, the method for preparing the modified carbon nanotubes includes: S1. Disperse multi-walled carbon nanotubes in a mixed solution of sulfuric acid and hydrogen peroxide and stir for 6-12 hours. Wash with deionized water until neutral and dry to obtain functionalized carbon nanotubes. S2. Functionalized carbon nanotubes and silane coupling agent KH-792 are added to an 80-95 wt% ethanol solution, stirred at 50-70℃ for 60-120 minutes, washed and dried to obtain modified carbon nanotubes.

[0021] Preferably, in step S1, the ratio of multi-walled carbon nanotubes to the sulfuric acid-hydrogen peroxide mixture is 1g:50~150mL; the sulfuric acid-hydrogen peroxide mixture is obtained by mixing 98wt% sulfuric acid and 30wt% hydrogen peroxide in a volume ratio of 4~6:1.

[0022] Preferably, in step S2, the ratio of functionalized carbon nanotubes, silane coupling agent KH-792, and ethanol solution is 1g:0.01~0.1g:50~150mL.

[0023] Preferably, in step five, the specific steps of spark plasma sintering include: loading powder into a mold, and placing the mold into a spark plasma sintering furnace for segmented heating and sintering.

[0024] Preferably, the segmented heating sintering specifically includes: First stage: Heat to 623~723K at a heating rate of 50~150K / min, and apply a pressure of 10~30MPa; Second stage: Heating to 773~853K at a heating rate of 30~100K / min, and increasing the pressure to 35~45MPa; The third stage: heat to 863-923K at a heating rate of 10-50K / min, increase the pressure to 45-55MPa, hold for 10-20 minutes, and then cool to room temperature at 5-15K / min.

[0025] Application of a PbTe-based thermoelectric material prepared by the method described above in thermoelectric energy conversion in the mid-temperature range (500K~900K).

[0026] Applications of PbTe-based thermoelectric materials prepared by the method described above in industrial waste heat recovery systems, automotive exhaust thermoelectric power generation devices, deep space probe isotope thermoelectric generators, and solid-state refrigeration devices.

[0027] This invention has at least the following beneficial effects: This invention prepares Pb by introducing excess Pb into n-type PbTe and co-doping with Zn. 1+x-y Te 0.996 I 0.004 - y Zn, through precise control of Pb excess concentration ( x = 0.002~0.012) and Zn doping amount ( y =0.01~0.04), combined with vacuum tube sealing technology and multi-stage sintering technology, the synergistic optimization of "defect repair-carrier transport-phonon scattering" was achieved, which solved the problems of low mobility and high thermal conductivity of traditional PbTe thermoelectric materials, significantly improved the thermoelectric performance of n-type PbTe, and the process is simple and controllable, suitable for large-scale production. It has important application prospects in the field of medium and high temperature thermoelectric conversion and provides an innovative solution for the development of high-performance thermoelectric materials.

[0028] 1) This invention improves carrier mobility and reduces lattice thermal conductivity by filling intrinsic vacancies with excess Pb and the synergistic effect of Zn doping, resulting in a ZT value of 1.08 at 823 K, which is significantly better than that of a single doping system.

[0029] 2) The preparation method of the present invention achieves its goal by precisely controlling the excess ratio of Pb ( x = 0.002~0.012) and Zn doping amount ( y =0.01~0.04), combined with the optimized multi-stage sintering process, the material properties can be controlled and adjusted.

[0030] 3) The use of high-vacuum sealing and precise annealing processes ensures the chemical homogeneity and structural stability of the materials, resulting in bulk materials with high density (≥97%) and good performance repeatability.

[0031] 4) Through multi-stage discharge plasma sintering technology, while ensuring high material density, the grain size and distribution of ZnTe nanophase are effectively controlled, and the electroacoustic transport performance is synergistically optimized.

[0032] 5) This invention, based on PbTe-based thermoelectric materials with excessive Pb and Zn doping, introduces modified carbon nanotube co-doping. This co-doping can simultaneously regulate the electrical and thermal transport properties of PbTe-based thermoelectric materials, further improving their thermoelectric performance and achieving a ZT value of 1.46 at 823 K. Specifically, carbon nanotubes are first functionalized using a sulfuric acid-hydrogen peroxide mixed solution. Then, the surface of the functionalized carbon nanotubes is modified using the silane coupling agent KH-792, effectively improving the dispersibility and stability of the carbon nanotubes. This allows for uniform doping, increases material density, improves the interfacial properties between the carbon nanotubes and the PbTe matrix, and regulates grain size, effectively improving the thermoelectric performance and structural stability of the material.

[0033] Other advantages, objectives and features of the present invention will become apparent in part from the following description, and in part from those skilled in the art through study and practice of the invention. Attached Figure Description

[0034] Figure 1 Pb prepared in Comparative Examples 2-8 of this invention 1+x Te 0.996 I 0.004 ( x XRD patterns of (0~0.012); Figure 2 Pb prepared in Examples 1-4 and Comparative Example 6 of this invention 1.010-y Te 0.996 I 0.004 - y XRD patterns of Zn (y=0~0.04); Figure 3 Pb prepared in Example 1 of this invention 0.990 Te 0.996 I 0.004 SEM image of -2%Zn; Figure 4 Pb prepared for Comparative Example 1 of this invention 0.980 Te 0.996 I 0.004 SEM image of -2%Zn; Figure 5 Pb prepared as Comparative Example 2 of this invention 1.002 Te 0.996 I 0.004 SEM image; Figure 6 Pb prepared as Comparative Example 8 of this invention 1.000 Te 0.996 I 0.004 SEM image; Figure 7 Pb prepared as Comparative Example 10 of this invention0.990 Te 0.996 I 0.004 SEM image of -2%Zn-S; Figure 8 Pb prepared in Comparative Examples 2-8 of this invention 1+x Te 0.996 I 0.004 ( x Mobility curves (=0~0.012); Figure 9 Pb prepared in Examples 1-4 and Comparative Example 6 of this invention 1.010-y Te 0.996 I 0.004 - y Zn ( y Thermal conductivity curves (0~0.04); Figure 10 Pb prepared in Examples 1-4 and Comparative Example 6 of this invention 1.010-y Te 0.996 I 0.004 - y Zn ( y =0~0.04) thermoelectric performance ZT value. Detailed Implementation

[0035] The present invention will now be described in further detail with reference to the accompanying drawings, so that those skilled in the art can implement it based on the description.

[0036] It should be understood that terms such as “having,” “comprising,” and “including” as used herein do not exclude the presence or addition of one or more other elements or combinations thereof.

[0037] Example 1 ( x =0.010, y =0.02) A method for preparing a PbTe-based thermoelectric material includes the following steps: Step 1: Accurately weigh Pb powder (99.99%), Te powder (99.99%), PbI2 powder (99.99%), and Zn powder (99.99%) according to the molar ratio of Pb : Te : PbI2 : Zn = 0.988 : 0.996 : 0.002 : 0.02; place the weighed powders in a glove box filled with high-purity argon gas, and premix them using an agate mortar for 30 minutes, pausing for 2 minutes every 5 minutes of grinding to prevent local overheating, to obtain a mixed powder; Step 2: Load the mixed powder into a high-purity quartz tube with an inner diameter of 20 mm and a wall thickness of 2 mm, connect it to the vacuum system, and turn on the mechanical pump and molecular pump in sequence. When the vacuum degree reaches 5 × 10⁻⁶, continue until the vacuum reaches 5 × 10⁻⁶. -4 At Pa, an oxyhydrogen flame is used for tube sealing; Step 3: Place the sealed quartz tube into a programmable temperature controlled box furnace, heat it to 673K ​​at 5K / min, hold it for 1 hour, then continue to heat it to 1273K at 8K / min, hold it for 6 hours. After holding, quickly remove the quartz tube and immerse it in ice-salt water for quenching at a cooling rate of about 200K / s. Then, place the quenched quartz tube into a programmable temperature controlled box furnace for annealing, heat it to 873K at 5K / min, and hold it for 48 hours. Step 4: Crush the ingot obtained in Step 3 and grind it through a 300-mesh sieve using an agate mortar and pestle. Pause for 2 minutes every 5 minutes of grinding to prevent local overheating. Load the powder into a graphite mold with an inner diameter of 10 mm and pre-press it to 20 MPa. Step 5: Place the graphite mold in the SPS and heat it to 673K ​​at 100K / min and 20MPa at 20MPa. Then heat it to 823K at 50K / min and 40MPa at 40MPa. Finally heat it to 873K at 30K / min and 50MPa at 50MPa. Hold it at this temperature for 15 minutes and then cool it to room temperature at 10K / min. Step 6: Remove the sample from the mold, grind and polish it to obtain the PbTe-based thermoelectric material, denoted as PbTe. 0.990 Te 0.996 I 0.004 -2%Zn.

[0038] Example 2 ( x =0.010, y =0.01) Pb powder (99.99%), Te powder (99.99%), PbI2 powder (99.99%), and Zn powder (99.99%) were accurately weighed according to the molar ratio of Pb:Te:PbI2:Zn = 0.998:0.996:0.002:0.01; the remaining steps were the same as in Example 1, to obtain a PbTe-based thermoelectric material, denoted as PbTe. 1.000 Te 0.996 I 0.004 -1%Zn.

[0039] Example 3 ( x =0.010, y =0.03) In this comparative example, Pb powder (99.99%), Te powder (99.99%), PbI2 powder (99.99%), and Zn powder (99.99%) were accurately weighed according to the molar ratio of Pb:Te:PbI2:Zn = 0.978:0.996:0.002:0.03. The remaining steps were the same as in Example 1, resulting in a PbTe-based thermoelectric material, denoted as PbTe. 0.980 Te 0.996 I0.004 -3%Zn.

[0040] Example 4 ( x =0.010, y =0.04) Pb powder (99.99%), Te powder (99.99%), PbI2 powder (99.99%), and Zn powder (99.99%) were accurately weighed according to the molar ratio of Pb:Te:PbI2:Zn = 0.968:0.996:0.002:0.04; the remaining steps were the same as in Example 1, to obtain a PbTe-based thermoelectric material, denoted as PbTe. 0.970 Te 0.996 I 0.004 -4%Zn.

[0041] Example 5 ( x =0.002, y =0.02) Pb powder (99.99%), Te powder (99.99%), PbI2 powder (99.99%), and Zn powder (99.99%) were accurately weighed according to the molar ratio of Pb:Te:PbI2:Zn = 0.98:0.996:0.002:0.02; the remaining steps were the same as in Example 1, to obtain a PbTe-based thermoelectric material, denoted as PbTe. 0.982 Te 0.996 I 0.004 -2%Zn.

[0042] Example 6 ( x =0.004, y =0.02) In this comparative example, Pb powder (99.99%), Te powder (99.99%), PbI2 powder (99.99%), and Zn powder (99.99%) were accurately weighed according to the molar ratio of Pb:Te:PbI2:Zn = 0.982:0.996:0.002:0.02; the remaining steps were the same as in Example 1, resulting in a PbTe-based thermoelectric material, denoted as PbTe. 0.984 Te 0.996 I 0.004 -2%Zn.

[0043] Example 7 ( x =0.006, y =0.02) In this comparative example, Pb powder (99.99%), Te powder (99.99%), PbI2 powder (99.99%), and Zn powder (99.99%) were accurately weighed according to the molar ratio of Pb:Te:PbI2:Zn = 0.984:0.996:0.002:0.02; the remaining steps were the same as in Example 1, resulting in a PbTe-based thermoelectric material, denoted as PbTe. 0.986 Te 0.996 I 0.004 -2%Zn.

[0044] Example 8 ( x =0.008, y =0.02) In this comparative example, Pb powder (99.99%), Te powder (99.99%), PbI2 powder (99.99%), and Zn powder (99.99%) were accurately weighed according to the molar ratio of Pb:Te:PbI2:Zn = 0.986:0.996:0.002:0.02; the remaining steps were the same as in Example 1, resulting in a PbTe-based thermoelectric material, denoted as PbTe. 0.988 Te 0.996 I 0.004 -2%Zn.

[0045] Example 9 ( x =0.012, y =0.02) In this comparative example, Pb powder (99.99%), Te powder (99.99%), PbI2 powder (99.99%), and Zn powder (99.99%) were accurately weighed according to the molar ratio of Pb:Te:PbI2:Zn = 0.990:0.996:0.002:0.02; the remaining steps were the same as in Example 1, resulting in a PbTe-based thermoelectric material, denoted as PbTe. 0.992 Te 0.996 I 0.004 -2%Zn.

[0046] Example 10 This embodiment further introduces modified carbon nanotube co-doping into PbTe-based thermoelectric materials, including the following steps: Steps one through three are the same as in Example 1; Step 4: Crush the ingot obtained in Step 3 and grind it through a 300-mesh sieve using an agate mortar and pestle, pausing for 2 minutes every 5 minutes of grinding; mix the powder and modified carbon nanotubes at a mass ratio of 99.8:0.2 and place them in a ball mill jar, ball milling in both directions for 240 minutes under argon protection, with a ball-to-material ratio of 20:1, rotating forward and backward at 300 r / min, pausing for 5 minutes every 15 minutes; load the ball-milled mixture into a graphite mold with an inner diameter of 10 mm and pre-press it to 20 MPa; Step 5: Place the graphite mold in the SPS and heat it to 673K ​​at 100K / min and 20MPa at 20MPa. Then heat it to 823K at 50K / min and 40MPa at 40MPa. Finally heat it to 873K at 30K / min and 50MPa at 50MPa. Hold it at this temperature for 15 minutes and then cool it to room temperature at 10K / min. Step 6: Remove the sample from the mold, grind and polish it to obtain the PbTe-based thermoelectric material, denoted as PbTe. 0.990 Te 0.996 I 0.004 -2%Zn / 0.2wt%MC; The method for preparing the modified carbon nanotubes includes: S1. Disperse 1g of multi-walled carbon nanotubes (outer diameter 10~20nm, length 1~2μm) into 100mL of sulfuric acid and hydrogen peroxide mixed solution (98wt% sulfuric acid and 30wt% hydrogen peroxide mixed in a volume ratio of 5:1) and stir for 10 hours. Wash with deionized water until neutral and dry to obtain functionalized carbon nanotubes. S2. Add 1g of functionalized carbon nanotubes and 0.05g of silane coupling agent KH-792 to 100mL of 90wt% ethanol solution, stir at 60℃ for 90 minutes, wash and dry to obtain modified carbon nanotubes.

[0047] Example 11 In this embodiment, the mass ratio of powder to modified carbon nanotubes in step four is 99.9:0.1, and the remaining steps are the same as in Example 10; a PbTe-based thermoelectric material is obtained, denoted as PbTe. 0.990 Te 0.996 I 0.004 -2%Zn / 0.1wt%MC.

[0048] Example 12 In this embodiment, the mass ratio of powder to modified carbon nanotubes in step four is 99.7:0.3, and the remaining steps are the same as in Example 10; a PbTe-based thermoelectric material is obtained, denoted as PbTe. 0.990 Te 0.996 I 0.004 -2%Zn / 0.3wt%MC.

[0049] Example 13 In this embodiment, step four uses unmodified multi-walled carbon nanotubes, and the remaining steps are the same as in Example 10; a PbTe-based thermoelectric material is obtained, denoted as PbTe. 0.990 Te 0.996 I 0.004 -2%Zn / 0.2wt%C.

[0050] Example 14 In this embodiment, step four uses functionalized carbon nanotubes, and the remaining steps are the same as in Example 10; a PbTe-based thermoelectric material is obtained, denoted as PbTe. 0.990 Te 0.996 I 0.004 -2%Zn / 0.2wt%FC.

[0051] Example 15 In this embodiment, the method for preparing the modified carbon nanotubes includes: adding 1g of multi-walled carbon nanotubes (outer diameter 10~20nm, length 1~2μm) and 0.05g of silane coupling agent KH-792 to 100mL of 90wt% ethanol solution, stirring at 60℃ for 90 minutes, washing and drying to obtain modified carbon nanotubes; The remaining steps are the same as in Example 10; a PbTe-based thermoelectric material is obtained, denoted as PbTe. 0.990 Te 0.996 I 0.004 -2%Zn / 0.2wt%KC.

[0052] Example 16 In this embodiment, KH-550 is used instead of KH-792, and the remaining steps are the same as in Example 10; a PbTe-based thermoelectric material is obtained, denoted as PbTe. 0.990 Te 0.996 I 0.004 -2%Zn / 0.2wt%HC.

[0053] Comparative Example 1 ( x =0, y =0.02) In this comparative example, Pb powder (99.99%), Te powder (99.99%), PbI2 powder (99.99%), and Zn powder (99.99%) were accurately weighed according to the molar ratio of Pb:Te:PbI2:Zn = 0.978:0.996:0.002:0.02; the remaining steps were the same as in Example 1, resulting in a PbTe-based thermoelectric material, denoted as PbTe. 0.980 Te 0.996 I 0.004 -2%Zn; Compared to Example 1, this comparative example is a Zn-doped PbTe-based thermoelectric material without excessive Pb doping.

[0054] Comparative Example 2 ( x =0.002, y =0) Pb powder (99.99%), Te powder (99.99%), and PbI2 powder (99.99%) were accurately weighed according to the molar ratio of Pb:Te:PbI2 = 1.000:0.996:0.002; the remaining steps were the same as in Example 1 to obtain a PbTe-based thermoelectric material, denoted as PbTe. 1.002 Te 0.996 I 0.004 .

[0055] Comparative Example 3 ( x =0.004, y =0) Pb powder (99.99%), Te powder (99.99%), and PbI2 powder (99.99%) were accurately weighed according to the molar ratio of Pb:Te:PbI2 = 1.002:0.996:0.002; the remaining steps were the same as in Example 1, to obtain a PbTe-based thermoelectric material, denoted as PbTe. 1.004 Te 0.996 I 0.004 .

[0056] Comparative Example 4 ( x =0.006, y =0) Pb powder (99.99%), Te powder (99.99%), and PbI2 powder (99.99%) were accurately weighed according to the molar ratio of Pb:Te:PbI2 = 1.004:0.996:0.002; the remaining steps were the same as in Example 1, to obtain a PbTe-based thermoelectric material, denoted as PbTe. 1.006 Te 0.996 I 0.004 .

[0057] Comparative Example 5 ( x =0.008, y =0) Pb powder (99.99%), Te powder (99.99%), and PbI2 powder (99.99%) were accurately weighed according to the molar ratio of Pb:Te:PbI2 = 1.006:0.996:0.002; the remaining steps were the same as in Example 1, to obtain a PbTe-based thermoelectric material, denoted as PbTe. 1.008 Te 0.996 I 0.004 .

[0058] Comparative Example 6 ( x =0.010, y =0) Pb powder (99.99%), Te powder (99.99%), and PbI2 powder (99.99%) were accurately weighed according to the molar ratio of Pb:Te:PbI2 = 1.008:0.996:0.002; the remaining steps were the same as in Example 1, to obtain a PbTe-based thermoelectric material, denoted as PbTe. 1.010 Te 0.996 I 0.004 .

[0059] Comparative Example 7 ( x =0.012, y =0) Pb powder (99.99%), Te powder (99.99%), and PbI2 powder (99.99%) were accurately weighed according to the molar ratio of Pb:Te:PbI2 = 1.000:0.996:0.002; the remaining steps were the same as in Example 1 to obtain a PbTe-based thermoelectric material, denoted as PbTe. 1.012 Te 0.996 I 0.004 ; Compared to Examples 1, 5-9, Comparative Examples 2-7 are PbTe-based thermoelectric materials with excessive Pb doping and no Zn doping.

[0060] Comparative Example 8 ( x =0, y =0) In this comparative example, Pb powder (99.99%), Te powder (99.99%), and PbI2 powder (99.99%) were accurately weighed according to the molar ratio of Pb:Te:PbI2 = 0.998:0.996:0.002; the remaining steps were the same as in Example 1, to obtain a PbTe-based thermoelectric material, denoted as PbTe. 1.000 Te 0.996 I 0.004 ; Compared to Example 1, this comparative example does not contain excessive Pb and has no Zn doping.

[0061] Comparative Example 9 ( x =0.010, y =0.05) In this comparative example, Pb powder (99.99%), Te powder (99.99%), PbI2 powder (99.99%), and Zn powder (99.99%) were accurately weighed according to the molar ratio of Pb:Te:PbI2:Zn = 0.958:0.996:0.002:0.05. The remaining steps were the same as in Example 1, resulting in a PbTe-based thermoelectric material, denoted as PbTe. 0.960 Te 0.996 I 0.004-5%Zn.

[0062] Comparative Example 10 In this comparative example, a single SPS sintering process was used. Step five was replaced with: placing the graphite mold in the SPS, heating to 873 K at 100 K / min, applying a pressure of 50 MPa, holding at that temperature for 15 minutes, and then cooling to room temperature at 10 K / min; the remaining steps were the same as in Example 1, resulting in a PbTe-based thermoelectric material, denoted as PbTe. 0.990 Te 0.996 I 0.004 -2%Zn-S.

[0063] Figure 1 Pb prepared for comparative examples 2-8 1+x Te 0.996 I 0.004 ( x The XRD patterns of PbTe (p0~0.012) are shown. It can be seen that the diffraction peaks of all samples correspond to the face-centered cubic structure of PbTe, with no peak shift and no obvious impurity or secondary phase characteristic peaks. This indicates that the introduction of excess Pb fills the gaps in the PbTe structure. 0.996 I 0.004 Intrinsic Pb vacancies in the parent body.

[0064] Figure 2 Pb prepared in Examples 1-4 and Comparative Example 6 1.010-y Te 0.996 I 0.004 - y XRD patterns of Zn (y=0~0.04) are shown. It can be seen that the characteristic peaks of all samples belong to the face-centered cubic structure of PbTe. Furthermore, with increasing Zn doping content, the characteristic peaks gradually shift to the right, indicating a decrease in cell parameters. This is because the smaller metal radius of Zn after doping... 2+ (1.13 Å) replaced the larger radius Pb 2+ (1.75Å).

[0065] Figure 3 Pb prepared in Example 1 0.990 Te 0.996 I 0.004 SEM image of -2% Zn. It can be seen that after Zn doping, ZnTe nanophase (scale approximately 100~500nm) appears and is uniformly distributed.

[0066] Figure 4 Pb prepared for Comparative Example 1 0.980 Te 0.996 I 0.004 SEM image of -2% Zn. Because Zn doping induces the formation of ZnTe, the presence of the ZnTe secondary phase can be seen.

[0067] Figure 5 Pb prepared for Comparative Example 2 1.002 Te 0.996 I 0.004 The SEM images show no obvious secondary phases because there is no Zn doping. Furthermore, the introduction of excess Pb only fills Pb vacancies and does not induce the formation of secondary phases; therefore, no Pb secondary phases are observed.

[0068] Figure 6 Pb prepared for Comparative Example 8 1.000 Te 0.996 I 0.004 The SEM images show no obvious secondary phase.

[0069] Figure 7 Pb prepared for Comparative Example 10 0.990 Te 0.996 I 0.004 The SEM image of -2% Zn-S shows that the grain size is uneven, and the grain boundary gaps are large, indicating the presence of pores. This suggests that a single SPS sintering process is insufficient to achieve sample densification, with a density of only 93.96%. In contrast, the samples from Examples 1-10, sintered using multi-stage SPS, exhibit uniform grain size, no obvious pores or gaps, and high densification, with densities of 97.95%, 99.04%, 98.90%, 98.80%, 99.21%, 97.66%, 98.15%, 98.11%, 97.76%, and 99.52%, respectively.

[0070] Figure 8 Pb prepared for comparative examples 2-8 1+x Te 0.996 I 0.004 ( x The mobility curves (=0~0.012) show that excess Pb increases the mobility of Pb. 1+x Te 0.996 I 0.004 The effect on sample carrier mobility. Improving mobility has always been a challenge in the field of thermoelectric materials. It can be seen that with the introduction of excess Pb, in... x When Pb ≤ 0.010, 1+x Te 0.996 I 0.004 The carrier mobility of the sample gradually increases, x The optimal value is reached when the value is 0.010.

[0071] Figure 9 Pb prepared in Examples 1-4 and Comparative Example 6 1.010-y Te 0.996 I 0.004 - y Zn ( yThe figure shows the thermal conductivity curves for Zn (0~0.04). As can be seen from the figure, the lattice thermal conductivity decreases significantly with increasing Zn doping content, indicating that Zn doping can effectively scatter phonons and reduce thermal conductivity.

[0072] Figure 10 Pb prepared in Examples 1-4 and Comparative Example 6 1.010-y Te 0.996 I 0.004 - y Zn ( y The thermoelectric ZT value (=0~0.04) after optimizing mobility, with Zn doping, in y The ZT value reaches its maximum when the value is 0.02.

[0073] The performance test results of Examples 1-9 and Comparative Examples 1-10 are shown in Table 1. It can be seen that the present invention, through the synergistic effect of excess Pb filling intrinsic vacancies and Zn doping, both improves carrier mobility and reduces lattice thermal conductivity, by precisely controlling the excess Pb ratio (…). x = 0.010) and Zn doping amount ( y =0.02), combined with the optimized multi-stage sintering process, the ZT value reached 1.08 at 823K, which is significantly better than the single-doped system and the undoped system.

[0074] Table 1 This invention, based on PbTe-based thermoelectric materials with excessive Pb and Zn doping, introduces modified carbon nanotube co-doping to further improve the thermoelectric performance of PbTe-based thermoelectric materials. The ZT values ​​at 823 K for Examples 10-16 are 1.46, 1.40, 1.42, 1.13, 1.25, 1.28, and 1.39, respectively. Among them, the PbTe prepared in Example 10... 0.990 Te 0.996 I 0.004 -2%Zn / 0.2wt%MC exhibits the best performance, with a higher average ZT value across the entire temperature range, reaching 1.46 at 823K, significantly higher than Example 1 (1.08).

[0075] Although embodiments of the present invention have been disclosed above, they are not limited to the applications listed in the specification and embodiments. They can be applied to various fields suitable for the present invention. For those skilled in the art, other modifications can be easily made. Therefore, without departing from the general concept defined by the claims and their equivalents, the present invention is not limited to the specific details and illustrations shown and described herein.

Claims

1. A PbTe-based thermoelectric material, characterized in that, Its chemical composition is Pb 1+x-y Te 0.996 I 0.004 - y Zn; in, x The value is between 0.002 and 0.

012. y The value is between 0.01 and 0.

04.

2. A method for preparing a PbTe-based thermoelectric material as described in claim 1, characterized in that, Includes the following steps: Step 1: Mix and grind Pb powder, Te powder, PbI2 powder and Zn powder to obtain a mixed powder; Step 2: Load the mixed powder into a quartz tube and seal it under vacuum; Step 3: The sealed quartz tube from Step 2 is subjected to high-temperature melting, water quenching and cooling, and annealing to obtain an ingot; Step 4: Crush and grind the ingot prepared in Step 3 into powder; Step 5: Perform spark plasma sintering on the powder from Step 4 to obtain PbTe-based thermoelectric material PbTe. 1+x- y Te 0.996 I 0.004 - y Zn.

3. The method for preparing the PbTe-based thermoelectric material as described in claim 2, characterized in that, In step one, the grinding is carried out under argon protection for 20 to 60 minutes, with a 2-minute pause every 5 minutes of grinding.

4. The method for preparing the PbTe-based thermoelectric material as described in claim 2, characterized in that, In step two, the specific steps of vacuum sealing include: loading the mixed powder into the quartz tube, connecting it to the vacuum system, and evacuating it to a vacuum level of 1×10⁻⁶. -4 ~1×10 -3 Pa, is sealed using an oxyhydrogen flame.

5. The method for preparing the PbTe-based thermoelectric material as described in claim 2, characterized in that, In step three, the specific steps of high-temperature melting include: heating to 573-773K at a heating rate of 3-10K / min, holding at that temperature for 0.5-2 hours, then heating to 1173-1373K and holding at that temperature for 4-8 hours.

6. The method for preparing the PbTe-based thermoelectric material as described in claim 2, characterized in that, In step three, the specific steps of water quenching include: taking out the quartz tube and immersing it in ice-salt water for quenching at a cooling rate of 100~300K / s; the specific steps of annealing include: heating the water-quenched quartz tube to 773~973K at a rate of 1~10K / min and holding it at that temperature for 36~60 hours.

7. The method for preparing the PbTe-based thermoelectric material as described in claim 2, characterized in that, In step four, the material is crushed and ground until it passes through a 200-400 mesh sieve.

8. The method for preparing the PbTe-based thermoelectric material as described in claim 2, characterized in that, In step five, the specific steps of spark plasma sintering include: loading powder into a mold, and placing the mold into a spark plasma sintering furnace for segmented heating and sintering.

9. The method for preparing the PbTe-based thermoelectric material as described in claim 8, characterized in that, The segmented heating sintering specifically includes: First stage: Heat to 623~723K at a heating rate of 50~150K / min, and apply a pressure of 10~30MPa; Second stage: Heating to 773~853K at a heating rate of 30~100K / min, and increasing the pressure to 35~45MPa; The third stage: heat to 863-923K at a heating rate of 10-50K / min, increase the pressure to 45-55MPa, hold for 10-20 minutes, and then cool to room temperature at 5-15K / min.

10. The application of a PbTe-based thermoelectric material prepared by the preparation method according to any one of claims 2-9 in industrial waste heat recovery systems, automotive exhaust thermoelectric power generation devices, deep space probe isotope thermoelectric generators, and solid-state refrigeration devices.